Cultural patterns of dying and death of selected minorities in the territory of the Czech Republic - Maňhalová, Jana; null, null; Tóthová, Valérie (STEF92 Technology Ltd., 2018)
Background: The objective of the submitted study was to find out and assess the specifics of transcultural features, rules and cultural patterns at dying and death in selected minorities in the Czech Republic in relation to nursing care, and to describe the experience of nurses with transcultural nursing and to evaluate the possibilities of using the Transcultural Assessment Model J. N. Giger and R. E. Davidhizar and the Conceptual Model of Cultural Competencies L. D. Purnell in transcultural aspects, rules and cultural patterns of dying and death in selected minorities in the Czech Republic. Methods: The stated objectives were achieved by a combination of qualitative and quantitative research methods, which were part of the research conducted with the financial support of the Grant Agency of the University of South Bohemia (GAJU) in České Budějovice within the team grant project called "Using Conceptual Models in Clinical and Community Practice ", No 048/2015 / S. In the first part of the research, a pre-research with 50 informants was carried out by a semi-structured interview technique, each time with 10 representatives of Judaism, Christianity, Buddhism, Islam and atheism. The main objective of the pre-research was to specify the key data for answering research questions and for creating a self-constructed questionnaire that served together with the standardized DAP-R questionnaire to complete quantitative data that analyzed the results of 1 700 respondents. Results: Based on the results of the pre-research study, it was found that the care of the dying and the dead is based on traditional values of human life. Quantitative research has shown that there is a statistically significant difference in transcultural features, rules and cultural patterns in the period of dying and death, depending on religion or personal belief, in which the degree of subjective identification with a religious belief or a personal belief plays an important role. The results have also shown the presence of lower fears of death in women than men, which can also be seen from the results of the DAP-R questionnaire, which show that there is a statistically significant difference in the welcome acceptance of death by gender. The welcome acceptance to death is more expressed in believers than non-believers people. The focus group with nurses appears to have revealed the absence of cultural competencies that can greatly influence the quality of life of dying people and their families. Conclusion: The results brought lot of variables which are worth our concern. The results showed that aspects of dying and death are mostly taboo by the society yet they are the natural part of human life. The results have also revealed the importance of spirituality and attitudes to death, whose understanding helps provide comprehensive care for the dying based on the holistic theory, and thus enables nurses to improve the quality of life of the patients in their difficult time.
Keywords: cultural patterns; dying; death; minorities